Parietal foramina with cleidocranial dysplasia is caused by mutation in MSX2. - Garcia-Miñaur, S; Mavrogiannis, L; Rannan-Eliya, S; Hendry, M; Liston, W; Porteous, M; Wilkie, A (2003)
The combination of skull defects in the form of enlarged parietal foramina (PFM) and deficient ossification of the clavicles is known as parietal foramina with cleidocranial dysplasia (PFMCCD). It is considered to be distinct from classical cleidocranial dysplasia (CCD) and is listed as a separate OMIM entry (168550). So far, only two families have been reported and the molecular basis of the disorder is unknown. We present a third family with PFMCCD, comprising four affected individuals in three generations, and demonstrate that a heterozygous tetranucleotide duplication in the MSX2 homeobox gene (505_508dupATTG) segregates with the phenotype. PFMCCD is indeed aetiologically distinct from CCD, which is caused by mutations in the RUNX2 gene, but allelic with isolated PFM, in which MSX2 mutations were previously identified. Our observations highlight the role of MSX2 in clavicular development and the importance of radiological examination of the clavicles in subjects with PFM.